Ceramide-based lipid profiles and the prevalence of type 2 diabetes differ between patients with coronary artery disease and those with peripheral artery disease. (3rd October 2022) - Leiherer, A; Muendlein, A; Brandtner, E; Saely, C H; Vonbank, A; Mader, A; Sprenger, L; Maechler, M; Jylha, A; Laaperi, M; Laaksonen, R; Maerz, W; et al.
Abstract: Introduction: Serum lipids and metabolic diseases, in particular type 2 diabetes (T2D) and non-alcoholic fatty liver disease (NAFLD), predict the atherosclerotic diseases coronary artery disease (CAD) and peripheral arterial disease (PAD). Purpose: The purpose of this study was to investigate in how far a more detailed characterization including serum lipids improves discrimination of PAD from CAD. Method: A cohort of 274 statin-naïve patients with either PAD (n=89) or stable CAD (n=185) were referred to metabolic screening and were characterized using nuclear magnetic resonance- and liquid chromatography-tandem mass spectrometry based advanced lipid and lipoprotein analysis. Results were validated in an independent cohort of 1239 patients with PAD or CAD. Results: We found a significant difference in T2D prevalence and in the ceramide-based lipid profile between PAD and CAD patients. However, neither cholesterol-based markers (including LDL-C, HDL-C) and detailed lipoprotein profiles nor the LD status differed significantly between PAD and CAD patients (figure). The difference between ceramide-based lipid profiles of CAD and PAD remained significant also after adjusting for body composition, smoking, inflammatory parameters, and T2D. Conclusion: We conclude that PAD and CAD differ in ceramide-based lipid profiles and T2D status, but not in other lipid characteristics or metabolic diseases. Funding Acknowledgement: Type of funding sources: None.